THE KING OF THE TOY COUNTRY - Nishonova Aksana (Galaxy International Interdisciplinary Research Journal, 2021)
Once upon a time, once upon a time. Not far from where we live, there is a king of toy countries. It has a magic mirror and flying wings, and every evening the king looks in the magic mirror at the toys of children all over the world. If a child does not pick up his toys after playing, the king puts his flying wings on his shoulders and sets off to pick them up. One day he looked in the mirror at a very upset toy of a girl named Sevara and set off.